(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Translating words between different languages is a complex process that involves understanding the nuances and rules of each language. When it comes to translating words between German and Uzbek, there are various forms of formations that play a crucial role in ensuring accurate and meaningful translations. This article aims to explore these forms of formation in detail.